2007
DOI: 10.1093/chromsci/45.4.169
|View full text |Cite
|
Sign up to set email alerts
|

Peak Alignment and Robust Principal Component Analysis of Gas Chromatograms of Fatty Acid Methyl Esters and Volatiles

Abstract: Gas chromatograms of fatty acid methyl esters and of volatile lipid oxidation products from fish lipid extracts are analyzed by multivariate data analysis [principal component analysis (PCA)]. Peak alignment is necessary in order to include all sampled points of the chromatograms in the data set. The ability of robust algorithms to deal with outlier problems, including both sample-wise and element-wise outliers, and the advantages and drawbacks of two robust PCA methods, robust PCA (ROBPCA) and robust singular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The correction is then conducted by warping these segments relatively to those of the reference profile. Hence, the linear stretching and compression of the length are carried out by shifting the end points with a limited number of data points, defined as the slack size (SS) [36]. The aim of this technique is to find the optimal correction that results in a maximum correlation with respect to the target fingerprint.…”
Section: Automated Correlation-optimized Warping (Acow)mentioning
confidence: 99%
“…The correction is then conducted by warping these segments relatively to those of the reference profile. Hence, the linear stretching and compression of the length are carried out by shifting the end points with a limited number of data points, defined as the slack size (SS) [36]. The aim of this technique is to find the optimal correction that results in a maximum correlation with respect to the target fingerprint.…”
Section: Automated Correlation-optimized Warping (Acow)mentioning
confidence: 99%
“…For that reason, more sophisticated methods, such as Grubbs’ test, exist (Grubbs 1969). Recently, it was shown that modern technologies such as robust principal component analysis (PCA) for GC (Hubert and Engelen 2004, Moller and Jorgensen 2007) and the independent component analysis (ICA) can be used to determine the possible outlier patterns (Baragona and Battaglia 2007). In any case before applying such tests, the data should be normalized, as most statistical procedures for determining outliers are dependent on a normal distribution of the data.…”
Section: Outliersmentioning
confidence: 99%
“…A plot of the first 2 principal components is therefore representative for data scattering in 2-dimensional space. 28 , 29 …”
Section: Methodsmentioning
confidence: 99%